Ischemic stroke in a young adult male as a manifestation of Takayasuâs arteritis - Indiyarti, Riani (Universa Medicina, 2008)
Takayasu arteritis is a chronic, inflammatory large vessel arteriopathy that primarily affects the aorta, its main branches, and the pulmonary arteries. Fibrosis and thickening of the arterial wall often occur in later stages, resulting in a cerebrovascular accident. A 20-year old man presented with ischemic stroke of young adults due to Takayasuâs arteritis, from which he had been suffering since childhood (age 10). Physical examination showed an abdominal aortic aneurysm, renal artery stenosis, leading to renovascular hypertension, and asymmetrical blood pressure. Aneurysm of abdominal aorta was diagnosed by panaorto-arteriography. Subsequently ischemic stroke of young adults developed, because the arteritis had led to stenosis of the left anterior and middle cerebral arteries, with renovascular hypertension as additional risk factor. On this patient a percutaneous transluminal angioplasty operation of the right renal artery was performed, and it is intended to do an extra-intracranial arterial bypass. Preventive treatment is necessary to stem the extension of the arteritis to other blood vessels.